2017
DOI: 10.21083/ajote.v5i1.3475
|View full text |Cite
|
Sign up to set email alerts
|

Are Basic School Head Teachers Transformational Leaders? Views of Teachers

Abstract: Transformational leadership practice is associated with improved school functioning and quality education delivery through teacher commitment and willingness to exceed targets or educational benchmarks (Balyer, 2012;Nedelcu, 2013). The establishment of the Leadership for Learning (LFL) program in Ghana in 2009 aimed at improving the effectiveness of basic school head teachers to better lead schools to promote student learning. In this study, the perceptions of basic school teachers as to the transformational l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…The results of the study also confirm the findings of past studies (Puni et al, 2018;Kellis & Ran, 2013;Shurbagi & Zahari, 2012b) who found that transformational leadership style has a statistically significant relationship with their employees' organizational commitment. In addition, our results also support the findings of Asare (2017) who also explored the relationship between transformational leadership and organizational commitment in the higher education context and found a positive significant relationship between transformational leadership and organizational commitment.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the study also confirm the findings of past studies (Puni et al, 2018;Kellis & Ran, 2013;Shurbagi & Zahari, 2012b) who found that transformational leadership style has a statistically significant relationship with their employees' organizational commitment. In addition, our results also support the findings of Asare (2017) who also explored the relationship between transformational leadership and organizational commitment in the higher education context and found a positive significant relationship between transformational leadership and organizational commitment.…”
Section: Discussionsupporting
confidence: 89%
“…As result, some teachers engage in self-fulfilling prophesies to please head teachers. Asare (2015) adds to Blase and Blase's (2002) report that head teachers' leadership behaviours are more of voluntary compulsion as teachers with dissenting views are expulsed from the school. As a result, teachers have no choice but to do as the head teachers demand.…”
Section: Statement Of the Problemmentioning
confidence: 97%
“…Leadership styles have significant effects on employees' commitment, which may lead to either the success or failure of an organization [19]. Transformational leadership has been widely researched and introduced as a result of changes in the education system [20].…”
Section: Introductionmentioning
confidence: 99%